PENGARUH KOMUNIKASI PERSUASIF TERHADAP SIKAP PATUH PEDAGANG KIOS CANDI BOROBUDUR PADA PROTOKOL KESEHATAN - Abdul Rachman Virga Maulidhany Yusuf; Jarot Prianggono (Bajang Institute, 2021)
Covid-19 has had a tremendous impact on the income of Borobudur Temple kiosk traders and has the potential to create other security and order problems. The discipline of the Borobudur Temple kiosk traders is one of the keys to attracting tourists so that tourists feel safe and comfortable while traveling in the Borobudur Temple Tourism Park Area. Persuasive communication is the best weapon to improve that discipline. The purpose of this study is to analyze the effect of persuasive communication on the obedient attitude of Borobudur Temple kiosk traders to the Covid-19 Health Protocol and describe the strategies carried out by health protocol advocates to influence the obedient attitude of Borobudur Temple kiosk traders to the Covid-19 health protocol. This study uses a mixed approach. The type of research used is survey and field research. Data collection techniques from questionnaires, interviews, observation and document review. Data analysis techniques through descriptive analysis, bivariate analysis, data reduction, verification and drawing conclusions. The sample in this study amounted to 91 kiosk traders of Borobudur Temple. The results of this study found that the Persuasive Communication variable showed a tcount value of 13,581 which was greater than the ttable value of 1,986 and a significant value of 0.000 <0.05. It can be concluded that persuasive communication has an effect on obedient attitude. The implementation of good strategies from health protocol advocates can affect positive changes in adherence. The selection of the right media is also an important factor that must be considered by communicators to provide invitations to the communicant.